Janubiy O‘zbekiston yer usti tuzilishining urbanizatsiya jarayonlari va shaharlar taraqqiyotiga ta’siri (SCIENCE and SOCIETY, 2025)
This article analyzes the influence of the surface structure (relief) of Southern Uzbekistan on urbanization processes and the development of cities based on geographical research. The study identifies how landforms, natural resources, geomorphological and hydrogeological factors affect the spatial distribution of cities, their functional growth, architectural-engineering design, and agglomeration processes. The urban potential of the region is evaluated through natural-geographic zoning.